Optimization of admixture and three-layer particleboard made from oil palm empty fruit bunch and rubberwood clones - Osman Al-Edrus, Syeed Saiful Azry; Md. Tahir, Paridah; Abdul Halip, Juliana (Springer International Publishing Switzerland, 2015)
Empty fruit bunch (EFB) is a biomass that is widely available and has the potential to be used as industrial raw material especially in wood-based industries. This study focuses on producing a particleboard by incorporating EFB with two different rubberwood clones: Prang Besar (PB) 260 and RRIM 2002, respectively. PB 260 is a commercially planted clone and wood from matured (>25 year-old) trees are used by wood-based panel manufacturers. RRIM 2002 is a new clone planted at the Malaysian Rubber Board (MRB) research trial plots and consists of only 4-year-old trees. Two types of particleboards (admixture and three-layer) with different ratios were produced. The Japanese Industrial Standard (JIS-5908 2003 particleboard) was used to evaluate mechanical and dimensional stability properties of the particleboards. From the study, it was found that admixture particleboards showed superior properties compared to three-layer particleboards. Layering EFB and rubberwood significantly decreased board performance for all properties (except internal bonding). The optimum ratios of EFB and both rubberwood clones are found to be 1:1 (50% EFB: 50% rubberwood). Meanwhile, increasing the rubberwood clones ratio to 70% lowered board performance especially for EFB (30%):RRIM 2002 clone (70%) boards which showed the lowest values for all properties for both admixture and three-layer boards